Treating depression in clinical practice: new insights on the multidisciplinary use of trazodone - Albert, Umberto; Tomasetti, Carmine; Marra, Camillo; Neviani, Francesca; Pirani, Alessandro; Taddeo, Daiana; Zanetti, Orazio; Maina, Giuseppe (Frontiers in Psychiatry, 2023)
Depression is estimated to be a leading contributor to the global mental health-related burden. The determinants of this huge prevalence lie in the fact that depressive symptoms may be comorbid in a wide variety of disorders, thus complicating and exacerbating their clinical framework. This makes the treatment of depressive symptoms difficult, since many pharmacological interactions should be considered by physicians planning therapy. Hence, depression still represents a challenge for both psychiatrists and other clinicians, in terms of its high rates of relapse and resistance despite well-established protocols. It is also complicated by the well-known latency in its complete response to current antidepressant treatments. In this context, the search for new strategies regarding antidepressant treatment is mandatory. Revising the use of “old” pharmacotherapies by considering their specific features may help to perfecting the treatment of depression, both in its standalone psychiatric manifestation and in the framework of other clinical conditions. Using a Nominal Group Technique approach, the results of a consensus of expert physicians regarding the possible use of trazodone as a valuable strategy for addressing the “real world” unmet needs of depression treatment in different fields (Psychiatry, Primary care, Neurology and Geriatrics) is herein provided. This idea is based on the unique characteristics of this drug which delivers a more rapid antidepressant action as compared to other selective serotonin reuptake inhibitors. It also has pharmacodynamic malleability (i.e. the possibility of exerting different effects on depressive symptoms at different dosages) and pharmacokinetic tolerability (i.e. the possibility of being used as an add-on to other antidepressants with scarce interaction and achieving complimentary effects) when used in the milieu of other drugs in treating comorbid depressive symptoms. Moreover, the large number of formulations available permits finite dosage adjustments, and the use of trazodone for specific pathologies, such as dysphagia. Therefore, although additional studies exploring the real-world conditions of antidepressant treatment are warranted, experts agree on the idea that depressive disorder, in both its standalone and its comorbid manifestations, may surely take advantage of the particular characteristics of trazodone, thus attempting to reach the greatest effectiveness in different contexts.